Effects of subjective effort on ball speed and spin in table tennis forehand topspin strokes - Sato, Y.; Wakui, K.; Miyazaki, K.; Ushiyama, Y. (International Journal of Sports Science & Coaching, 2025)
This study investigated how modulating subjective effort influences ball speed and spin rate in table tennis forehand topspin strokes, and examined discrepancies between perceived and actual output. Ten skilled male collegiate players performed strokes at five effort levels (60%, 70%, 80%, 90%, 100%). Objective measures included ball speed and spin rate, while subjective assessments involved introspective ratings of perceived control and strain. Both ball speed and spin rate generally increased with effort, indicating partial success in output modulation. However, under lower effort conditions—particularly for spin—participants exhibited excessive and unstable output, highlighting the difficulty of intentional suppression. Perceived strain increased linearly, while perceived control followed a nonlinear trend, with individual variation and a notable drop at 100%. Performance reproducibility, assessed via coefficient of variation, showed ball speed was less stable at lower efforts, while spin rate peaked in variability at 90%, indicating distinct challenges in regulating output types. These findings suggest that suppressing force demands more refined sensory calibration and self-monitoring than exerting it. Notably, "hitting softly" proved more difficult than maximizing effort, reframing motor control as the regulation rather than the amplification of force. From a practical perspective, training strategies such as visualizing subjective-objective mismatches, setting goals for reproducibility and suppression, and monitoring perceived control and strain may support more stable and self-regulated performance. Incorporating such approaches into coaching could enhance adaptability under variable or high-pressure conditions. This study provides a foundation for perceptual and introspective training strategies that prioritize modulation over maximization in racket sports.